Research and application of IPTV precision marketing based on big data - Hongyong YU; Jianfeng WEN; Xin CAI; Chenxu QIU (Dianxin kexue)
The big data technology in IPTV precision marketing was analyzed. According to local conditions, the framework solution of“Hadoop big data platform + Web crawler + modeling tool”was developed. The key points of the solution and the whole data modeling process were analyzed. Good results were achieved in IPTV precision marketing, and higher application value was gained.